2010
DOI: 10.1002/prot.22882
|View full text |Cite
|
Sign up to set email alerts
|

Improved identification of outer membrane beta barrel proteins using primary sequence, predicted secondary structure, and evolutionary information

Abstract: Membrane proteins (MPs) are difficult to identify in genomes and to crystallize, making it hard to determine their tertiary structures. MPs could be categorized into α-helical (AMP) and outer membrane proteins which mostly include beta barrel folds (OMBBs). The AMPs are relatively easy to predict from a protein sequence because they usually include several long membrane-spanning hydrophobic α-helices. The OMBBs play important roles in cell biology, they are targeted by multiple drugs, and they are more challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Because the T. pallidum genome does not encode orthologs for known OMPs of proteobacteria other than TP0326/BamA (22), in silico identification of ␤-barrels rests upon structural predictions. Whereas the ␣-helical transmembrane domains of IM proteins are readily identifiable, such is not the case for the membrane-spanning elements (i.e., amphipathic ␤-strands) of OMPs (41,56,63).…”
mentioning
confidence: 99%
“…Because the T. pallidum genome does not encode orthologs for known OMPs of proteobacteria other than TP0326/BamA (22), in silico identification of ␤-barrels rests upon structural predictions. Whereas the ␣-helical transmembrane domains of IM proteins are readily identifiable, such is not the case for the membrane-spanning elements (i.e., amphipathic ␤-strands) of OMPs (41,56,63).…”
mentioning
confidence: 99%
“…Each element in the PSSM represents the probability of each residue position in the multiple sequence alignment. Plenty of previous studies have shown that multiple sequence alignments in the form of PSSM can substantially improve overall prediction performance [ 35 38 ]. In this article, the PSSM profile for each protein sequence is generated with default parameters (3 iterations and 0.001 of E-value cutoff) against the non-redundant (nr) dataset obtained from the NCBI.…”
Section: Methodsmentioning
confidence: 99%
“…Classification protocol SVM is a very powerful and popular method for supervised pattern recognition and has been widely used in the realm of bioinformatics [3,6,29,37,38,42,[44][45][46]. To handle a multiclass problem, the one-versus-one (OVO) and oneversus-rest (OVR) approaches are generally applied to extend traditional SVM.…”
Section: Frequency Of Reduced Amino Acid Alphabetmentioning
confidence: 99%